AN ANALYSIS OF STUDENTS’ SCANNING SKILL IN READING TEXT AT SECOND GRADE STUDENTS OF MTs THAMRIN YAHYA RAMBAH HILIR - Wirda Jannatul Jannah (English Study Program University of Pasir Pengaraian, 2021)
The purpose of this research was to find out the second grade students’scanning skill in reading text at MTs Thamrin Yahya Rambah Hilir. The research design was a descriptive qualitative. The population was second grade students with total number of 77 students and the sample were 26 students. The sample was taken by cluster random sampling. In collecting the data the researcher used reading test it was narrative text to got the data. In analyzing the data the researcher used the components of Narrative Text such as Orientation, Complication, and Resolution. Based on the result of analysiss, the researcher found 4 students (15,3%) had excellent level, 7 students (26,9%) had good level, 11 students (42,3%) had average level, and 4 students (15,3%) had fair level and there were no students who got poor category. It means that students’ scanning skill in narrative text at second grade students of MTs Thamrin Yahya was average.